His favorites - Walbert, Kate, 1961- (Scribner, 2018)
"They were on a lark, three teenaged girls speeding across the greens on a “borrowed” golf cart, at night, drunk. The cart crashes and one of the girls lands violently in the rough, killed instantly. The driver, Jo, flees the hometown that has turned against her and enrolls at a prestigious boarding school. Her past weighs on her. She is responsible for the death of her best friend. She has tipped her parent's rocky marriage into demise. She is ready to begin again, far away from the accident. Taut, propulsive and devastating, His Favorites reveals the interior life of a young woman determined to navigate the treachery in a new world. Told from her perspective many years later, the story cooly describes a series of shattering events and the system that failed to protect her." -- Publisher annotation.